PEMANFAATAN CHATGPT DALAM PEMBELAJARAN MATEMATIKA UNTUK MENGANALISIS PENGALAMAN BELAJAR DAN KESULITAN SISWA - Aminullah; Nur Baeti (Jurnal Ilmiah Matematika Realistik, 2026)
The purpose of this study was to analyze students’ learning experiences and difficulties in using ChatGPT in mathematics instruction. The study employed a descriptive qualitative approach with subjects selected through purposive sampling, specifically students who had already utilized ChatGPT as a learning tool. Data were collected through observation, semi-structured interviews and documentation. The research focused on how students used ChatGPT, their understanding of solution steps, their ability to rephrase the process and the difficulties they faced in solving math problems. The results indicated that ChatGPT use tended to be result-oriented, with students directly copying answers without understanding the solution steps. Students also struggled to comprehend explanations, rephrase the process and solve problems with varying formats. Additionally, there are differences in students’ abilities to utilize ChatGPT, leading to variations in learning experiences. These findings suggest that the use of ChatGPT has not yet fully supported the development of students’ conceptual understanding. Therefore, a more targeted management of ChatGPT usage is needed so that it does not merely focus on results but also fosters an understanding of the thinking process and concept formation in mathematics learning.